Implementation Of Environmental Management System And Pro-Environmental Behaviour To Achieve Sustainable Industrial Performance For Hotels - Rainanto, Bambang Hengky; Qhalby, Juwita (Jurnal Ilmiah Manajemen Kesatuan, 2019)
The COVID-19 pandemic has affected the world of tourism, especially in the hotel industry. Movement and travel restrictions, changes in human behaviour while traveling, as well as the existence of several regulations from the central government of Indonesia and local governments affect tourist visits and occupancy rates in hotels. As in large and star hotels, small hotels and non-star hotels have also been affected by the COVID-19 pandemic. This research was conducted in East Java Province, Indonesia, involving 161 non-star hotels during the data collection period in March and April 2020, namely in the early months of the Covid-19 Pandemic in Indonesia. The measurement parameters for the independent variables are Environmental Management System (EMS) and Pro-Environmental Behaviour (PEB), while the dependent variable is Sustainable Industry Performance. Research analysis using Smart-PLS 2.0. The conclusions of this study indicate that in the early months of the COVID-19 pandemic the Environmental Management System and Pro-Environmental Behaviour had a significant and positive effect on Economic Sustainability, with the strongest influence being given by Pro-Environmental Behaviour; only Pro-Environmental Behaviour has a significant and positive influence on Environmental Sustainability; Environmental Management System and Pro-Environmental Behaviour have a significant and positive influence on Social Sustainability, with the strongest influence exerted by the Environmental Management System. Keywords: Environmental Management System (EMS), Pro-Environmental Behaviour (PEB), Sustainable Industrial Performance, Non-Star Hotels, COVID-19 Pandemic